Basic Measures of Auditory Perception in Children: No Evidence for Mediation by Auditory Working Memory Capacity - Mishra, Srikanta K.; Saxena, Udit (Frontiers in Human Neuroscience, 2020)
Immature auditory perception in children has generally been ascribed to deficiencies in cognitive factors, such as working memory and inattention. This notion appears to be commonly accepted for all children despite limited empirical evidence. In the present work, we examined whether working memory capacity would predict basic aspects of hearing, pure-tone frequency discrimination and temporal gap detection, in typically-developing, normal-hearing children (7-12 years). Contrary to our expectation, working memory capacity, as measured by digit spans, or intrinsic auditory attention (on- and off-task response variability) did not consistently predict the individual variability in auditory perception. Present results provide no evidence for a role of working memory capacity in basic measures of auditory perception in children. This lack of a relationship may partly explain why some children with perceptual deficits despite normal audiograms (commonly referred to as auditory processing disorders) may have typical cognitive abilities.